2005
DOI: 10.1007/s10800-005-9073-z
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of aluminium metal matrix composites reinforced with TiC processed by pressureless melt infiltration

Abstract: The corrosion resistance of commercial aluminium alloy (2024) and binary Al-Cu x and Al-Mg x alloys reinforced with TiC particles using a pressureless infiltration method has been evaluated in 3.5% NaCl solution using potentiodynamic polarization curves and linear polarization resistance measurements. The TiC preforms were sintered at 1250, 1350 and 1450°C and infiltrated in the range of 900-1200°C under argon atmosphere. Some specimens were heat treated at 530°C for 150 min, water quenched and subsequently ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 22 publications
(27 reference statements)
2
21
0
Order By: Relevance
“…With the increase of magnesium content, the E corr of the Gr f /Al composite decreased sharply because the E corr of magnesium (-1.84 V, saturated calomel electrode, SCE) is lower than that of Al (-0.83.V SCE). This result is consistent with Albiter et al's [8] investigation on TiC p /Al composites of different magnesium contents. It should be noted that the i corr of Gr f /Al-3.2Mg was the lowest, which indicated that Gr f /Al-3.2Mg has the best corrosion resistance among the four composites.…”
Section: Methodssupporting
confidence: 93%
“…With the increase of magnesium content, the E corr of the Gr f /Al composite decreased sharply because the E corr of magnesium (-1.84 V, saturated calomel electrode, SCE) is lower than that of Al (-0.83.V SCE). This result is consistent with Albiter et al's [8] investigation on TiC p /Al composites of different magnesium contents. It should be noted that the i corr of Gr f /Al-3.2Mg was the lowest, which indicated that Gr f /Al-3.2Mg has the best corrosion resistance among the four composites.…”
Section: Methodssupporting
confidence: 93%
“…It can be seen that A535 alloy has superior pitting corrosion resistance to the composites. The corrosion behaviour of particulate Al MMCs is influenced by several factors such as porosity, high dislocation densities at the matrix-reinforcement interfaces, the presence of intermetallic compounds (IMCs) and reaction products, and the electrical conductivity of the reinforcing phases [19]. Gikunoo and Oguocha [24] have reported that the amount of dimagnesium silicide, Mg 2 Plot of E p -E corr for A535 alloy and its MMCs in 3.5wt% NaCl solution (pH = 7).…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion behaviour of Al-based MMCs reinforced with particles such as Al 2 O 3 , garnet, TiC, AlN and SiC particles have been studied by several workers [12][13][14][15][16][17][18][19][20][21]. A close look at the results obtained from these studies shows that three types of corrosion can occur in particulate Al MMCs at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, many works reported that the corrosion resistance of composites was higher than that for their alloys. [34][35][36] …”
Section: B Surface and Subsurface Microhardness Evaluationmentioning
confidence: 99%